The Customer Acceptance of Online Insurance in Malaysia - Tan, Chye Ting (2012)
Over a decade ago, when Internet technology became a major influence in people’s life; where information could flow freely and rapidly, Information Technology significantly changed the way business is done. Many researchers have dedicated effort and time into the research of technology acceptance among consumer. As a result, many theories and model of technology acceptance are developed to predict and explain user behavior. This research draws upon the Technology Acceptance Model to investigate the acceptance of online insurance among Malaysian consumers. This thesis (1) reviewed previous literature on IT acceptance with more detailed focus on Technology Acceptance Model (Davis, 1989), (2)investigated the utilization of online insurance by consumers in Malaysia insurance industry and the intention to use online insurance to perform transactions, (3) examined whether consumers’ prior experience with internet banking will influence their acceptance to online insurance, (4) proved that perceived security and perceived privacy does affect user acceptance of online insurance. Questionnaire survey was provided to the public and yielded 200 respondents. Sample ttests were used to analyze result of the survey. From the findings, perceived usefulness and perceived ease of use significantly influence the usage behaviour in terms of intentions. In addition, two moderators: socio-demographics (e.g age, highest level of education and industry), and prior experience in banking impacted the influence of key determinants towards usage intentions. In conclusion, the acceptance of online insurance among Malaysian consumer is very encouraging.